Family reports of medically impaired drivers in Missouri: Cognitive concerns and licensing outcomes. (January 2015) - Meuser, Thomas M.; Carr, David B.; Unger, Elizabeth A.; Ulfarsson, Gudmundur F.
Highlights: About 52% of family reported drivers had cognitive impairment noted as medical fact. More than 50% of those reported by family did not continue assessment. Family reports of Alzheimer's disease, 100% match with physician diagnosis. Family reports of other cognitive impairment, 75% match with physicians. Only about 2% of reported drivers retained their driver's license. Abstract: This study investigated reasons why older adults ( n  = 689) were reported to the Driver License Bureau, Missouri Department of Revenue, by family members as potentially unfit to drive with an emphasis on cognitive concerns and associated licensing outcomes. A total of 448 drivers were reported to have some cognitive issue; common symptoms included confusion, memory loss, and becoming lost while driving. Diagnostic labels (Alzheimer's disease (AD), cognitive impairment/dementia, brain injury/insult) were listed for 365 cases. A physician evaluation is required for license review. Of those with a diagnostic label, half (51%, n  = 187) failed to submit this evaluation and almost all were de-licensed immediately. Of those evaluated by a physician, diagnostic agreement between family members and physicians was high for specific conditions (100% for AD, 97% for acute brain injury), and less so for cognitive impairment/dementia (75%). This latter finding suggests that physicians and family members may understand cognitive symptoms differently. Whether cognitively impaired or not, few family reported drivers in this sample (∼2%) retained a valid license. Family members may be in the best position to recognize when medical-functional deficits impact on driving safety, and physicians and driver licensing authorities would do well to take their observations into account with respect to older driver fitness.